Determinants of quality of life in young onset dementia – results from a European multicenter assessment. (2nd January 2017) - Millenaar, Joany; Hvidsten, Lara; de Vugt, Marjolein E.; Engedal, Knut; Selbæk, Geir; Wyller, Torgeir Bruun; Johannessen, Aud; Haugen, Per Kristian; Bakker, Christian; van Vliet, Deliane; Koopmans, Raymond T.C.M.; Verhey, Frans R.J.; et al.
ABSTRACT: Background: Promoting adaptation, improving well-being and maintaining an optimal quality of life (QOL) is an important aspect in dementia care. The purpose of this study was to identify determinants of QOL in young onset dementia, and to assess differences in QoL domains between people with Alzheimer's disease (AD) and frontotemporal dementia (FTD). Methods: In total 135 persons with AD and 58 persons with FTD were included from two prospective cohort studies. QOL was assessed with the proxy reported quality of life in Alzheimer's disease questionnaire (QoL-AD). Possible determinants were explored using multiple linear regression and included sociodemographic variables, diagnosis, dementia severity, disease awareness, neuropsychiatric symptoms, met and unmet needs and hours of personal and instrumental care. Differences between QOL domains in people with AD and FTD were calculated using Mann-Whitney U tests. Results: Lower QOL was associated with more depressive symptoms, lower disease awareness, and a higher amount of needs, both met and unmet. People with AD scored lower on the memory and higher on the friends' subscale. No differences were found for the other items. Conclusion: This study demonstrates a unique set of determinants of QOL in AD and FTD. Interventions directed towards these specific factors may improve QOL.